CHANGES IN SOME BIOPHYSICAL AND BIOCHEMICAL PARAMETERS IN BLOOD AND URINE OF WORKERS CHRONICALLY EXPOSED TO BENZENE - MA, Kotb; HS, Ramadan; El-Din R, Shams; HA, Motaweh; RR, Shehata; EA, El-Bassiouni (European Scientific Journal, ESJ, 2013)
Objective: Benzene may occur naturally as a component of petroleum, or may be manufactured synthetically. It is found in the environment as a contaminant from both human activities and natural processes, posing serious bio-hazards from chronic exposure. Methods: A total of 330 individual were enrolled to study possible health hazards of benzene contamination; 265 males occupationally chronically exposed to low levels of benzene in their daily activity were compared to 65 healthy individuals of the same socio-economic standard. Benzene workers were divided between 45 workers in printing shops, 70 subjects dealing with benzene containing paints (painters), 75 subjects working in professions related to automotive work (autoworkers) and 75 car drivers. Results: benzene itself was not detected in blood or urine of all participants, but the levels of its metabolites; phenol and t,t-muconic acid, were higher in the blood and urine samples in the group of benzene-exposed workers. The results also indicate that individuals in this group are under oxidative stress. However, neither the determined liver function nor the kidney function tests showed significant deviation from controls. However, the results of the ﻿biophysical hematological parameters, including the degree of hemolysis, blood viscosity, RBCs aggregation and form factor were significantly deviated from normal. Conclusion: The deviation of the determined biochemical and biophysical parameters from normal may predispose such workers to a variety of health problems. Early correction of the oxidative stress and the hematological parameters and improvement of working conditions are necessary to prevent their progress to more serious health conditions, especially in children and young adolescents working under similar conditions. Running Title : Chronic exposure to benzene in work place